Thalamocortical diaschisis: positron emission tomography in humans. - Baron, J C (1992)
To investigate further the relations between cortical energy metabolism and neuropsychological impairment after unilateral thalamic lesion, 55 patients underwent positron emission tomography studies of either cortical oxygen consumption or glucose utilisation, including eight repeat studies, at times ranging from 4 days to 98 months after the onset of the lesion [stroke (n = 44) or stereotaxic VL-Vim thalamotomy performed for movement disorders (n = 11)]. Patients with thalamotomy were also studied preoperatively and the surgery induced a significant fall in cortical metabolism on both sides (more so ipsilaterally); post-operatively the magnitude of the ipsilateral cortex hypometabolism was positively correlated to the severity of global neuropsychological impairment; similar but less significant findings were obtained for the ipsilateral/contralateral cortical metabolic asymmetry. With respect to the whole patient sample, the cortical metabolic asymmetry was initially pronounced, with subsequent monoexponential recovery, in the cognitively impaired study group, but it was only mild and showed no meaningful trend for recovery in the cognitively unaffected study group; yet even soon (< 3 months) after thalamic lesion there was a noticeable overlap of individual asymmetry values among the two study groups. These results lend further support to the view that the neuropsychological impairment that frequently follows unilateral thalamic lesions is reflected in a depression of synaptic activity in both the overlying and the contralateral cerebral cortices. For individual patients, this study also illustrates the potentially misleading nature of the measured cortical metabolic asymmetry with respect to neuropsychological status, especially at late times after lesion, in part because side to side metabolic ratios do not reflect bilateral changes.